Trends and Directions of TPACK Research in Education: A Thematic Analysis of 26 Scopus-Indexed Articles from 2021–2025 - Neldarisasmita Neldarisasmita; Hardina Ullfa; Isni Rahma Apriyanti; Rayandra Asyhar; Ilham Falani (Pascasarjana, Mataram University, 2026)
This study aims to analyze the development of themes and focus of studies in recent research using the Technological Pedagogical Content Knowledge (TPACK) framework in the field of education. A total of 600 initial documents with the keyword